A model-based study of the wind regime over the Corinthian Gulf - I. Koletsis; V. Kotroni; K. Lagouvardos (Natural Hazards and Earth System Sciences, 2014)
The Corinthian Gulf is a narrow sea-level passage surrounded by a steep complex topography that consists of high mountains as well as elevated and sea-level gaps and straits. The complex terrain is expected to affect the wind flow in the area that often experiences high winds, with important consequences on the commercial and recreational activities over the gulf's maritime area. For that reason, a model-based study of the wind regime over the Corinthian Gulf has been created, as observational data over the area are recent and spatially sparse. Analysis of 5 yr of data from the fifth-generation Penn State/NCAR mesoscale model (MM5) model reveals that the wind regime of the gulf is greatly influenced by the topography. Easterly winds occur more frequently and are stronger in the maritime area in the western edge of the gulf, with a frequency of occurrence on the order of 70%. Moreover, the most intense wind events at this area occur during the winter season (December, January, and February). Finally the paper also provides a discussion on the synoptic patterns, which lead to the strongest wind events in the studied area.